EFFECT OF RESISTANCE EXERCISE WITH DIFFERENT MUSCLE ACTION DURATIONS ON LACTATE RESPONSE - Fernando Vitor Lima; Cinara Gonçalves Costa; Lucas Túlio de Lacerda; Lorena Viggiano Rocha da Silva; Rodrigo César Ribeiro Diniz; Hugo César Martins Costa; Frank Douglas Tourino; Mauro Heleno Chagas (Journal of Physical Education)
ABSTRACT The aim of this study was to compare the blood lactate concentration in strength training protocols with different muscle action durations in the bench press exercise. Seventeen volunteers performed three protocols with three sets of six repetitions at 60 % of 1RM, three- minute break between sets and different muscle action durations (2-4: 2s concentric and 4s eccentric; 3-3: 3s concentric and 3s eccentric; 4-2: 4s concentric and 2s eccentric). The analysis of blood lactate concentration considered the average values per set in each protocol. The ANOVA two-way of the results showed that the main effect for protocol showed no significant difference between the three protocols (F = 0,75; p = 0,48; power = 0,48; η2 = 0,17), as the interaction among the factors (F = 1,68; p = 0,13; power = 0,09; η2= 0,62). However, there was significant main effect for set (F = 320,23; p = 0,0001; power = 1,00; η2= 0,95). Therefore, resistance training protocols equated with different muscle actions durations shows no differences in blood lactate response and, regardless of the protocol, its concentration increased throughout the three sets performed.